A meta-analysis of the effects of communal livestock grazing on vegetation and soils in sub-Saharan Africa - Yayneshet, T.; Treydte, A.C. (Elsevier, 2015)
Extensive livestock grazing is one of the most common and widespread forms of land uses in sub Saharan Africa (SSA). Studies assessing the effects of extensive livestock grazing on vegetation and soils in SSA are inconsistent in the direction and magnitude of study outcomes. We applied meta-analysis to identify whether studies so far conducted in the rangeland systems of SSA have detected significant rangeland degradation as approximated by changes in vegetation attributes (reduction in species diversity and richness; decreased biomass and ground cover; increased woody species density and canopy cover) and soil properties (Decreased soil OC, N and P). We quantified results of the included studies using the response ratio, which is the log proportional change in the means of a treatment and a control group. Four moderator variables (elevation (<1500 and ≥1500 m above sea level); plant life form (herbaceous and woody), rainfall amount (<600 mm and ≥600 mm), rainfall modality (mono and bimodal), and soil texture (Loam, sandy, sandy loam)) appeared to affect the response of species diversity and richness patterns to different grazing regimes, i.e., communal grazing systems, exclosures, livestock ranches and game reserves. Species diversity and richness values were generally lower in the communal grazing systems compared to the other grazing regimes. Only three moderator variables (rainfall amount and modality, and soil texture) affected the herbaceous basal cover response. Differences in soil OC were highest between communal and exclosure areas, visible at high elevations and under high rainfall. Soil N was influenced by rainfall modality and soil texture. We conclude that the effects of grazing regimes onto the environment cannot be generalized but are specific across vegetation and soil variables and differ considerably with rainfall and elevation.